Vaginal fibroleiomyoma in a dog: a case report - Ng, Wen Chee; Hamzah, Hazilawati; Mohamed Mustapha, Noordin; Shamsudin, Shahirudin; Mohd Arip, Erni Wati (2012)
A 15 year-old, intact female, Pomeranian dog was presented to University Veterinary Hospital (UVH), Universiti Putra Malaysia (UPM) with a complaint of vaginal mass growth for the pass one year. Clinical findings of three pedunculated vaginal masses at the vaginal orifice were observed. Radiography findings revealed no metastasis of the lungs while ultrasonography findings revealed the extensiveness of the growth of the vaginal mass was 3.5 cm long. Cytological findings from the vaginal smear showed no characteristics of malignancy of the vaginal cells. Hence, the tentative diagnosis at that time was benign vaginal tumour. Treatment plan was to conduct episiotomy and biopsy of the vaginal mass. Histological examination indicated a fibroleiomyoma.